Adapting land administration to the institutional framework of customary tenure : the case of peri-urban Ghana - Arko-Adjei, Anthony (ITC publication, 2011)
"Historical experience in many Sub-Saharan African countries demonstrates that an alternative approach to conventional land administration methods is required to appropriately secure tenure and administer land rights in customary areas. This book is about dealing with the dynamics of customary tenure and with land governance and institutional capacity issues necessary to implement land administration at the local level. Methods for implementing land administration systems at the local level have been presented in a three-phased tenure model. The author concludes that customary tenure institutions have their own mechanisms for adapting to societal change and a desirable solution would therefore be to adapt land administration to the institutional framework of customary tenure. The information in this book will be essential for academic work in land administration in developing countries. It will prove a useful reference for policy makers and practitioners in the land administration field." --